Networked Language Communities: From Constructed Languages to Natural Languages - Marat N. Chistanov (Гуманитарный вектор)
Activities for the preservation and development of ethnic minority languages are considered as the most important part of the actions to preserve the cultural heritage of the peoples inhabiting the Russian Federation. The obligatory nature of such activities is enshrined in our country constitutionally. For the ethnic intelligentsia, any attempts to infringe on the linguistic rights of their peoples turn out to be very painful. This problem in domestic science is most often considered in the tradition of linguistic relativism. This approach comes from the Humboldtian tradition in linguistics and in modern practice is associated with the Sapir-Whorf hypothesis. With all the advantages of this approach, it is not without a number of disadvantages. The theory of a unique linguistic world view leads to the sacralization of the language, conserving and ritualizing it, depriving it of vitality. The situation with the functioning of regional languages will change either with the revitalization of old language communities, or with the formation of new language communities in which the language can function as a real means of communication and will gain a new lease on life. Accepting the fact that it is hardly possible to return to traditional economic systems in which the languages of ethnic minorities were rooted, it seems interesting to study the experience of the functioning of communities of modern artifi cial languages. The network forms of organization of such communities are interesting, because in the context of globalization, the emergence and functioning of local linguistic communities based on a geographical principle becomes diffi cult. This turn makes us take a different look at the problems of the functioning of natural and artifi cial languages: it is not its internal structure, semantics and syntactics that comes to the fore but the conditions for its use and the reasons that make people turn to it, that is, pragmatics. In other words, the problem of the viability of a language is not so much a question of its morphology and syntax, and not even a question of its expressive possibilities and means, but a question of the motives of people’s linguistic behavior.